Asymmetry of values, indigenous forces, and incumbent success in counterinsurgency: evidence from Chechnya - Aliyev, Huseyn (2015)
This article fills the gap in existing scholarship on asymmetric conflict, indigenous forces, and how socio-cultural codes shape the dynamics and outcomes of conflict transformation. Specifically, it identifies three key socio-cultural values commonplace in honorific societies: retaliation, hospitality, and silence. As sources of effective pro-insurgent violent mobilisation and support from among the local population, these values provide insurgents with an asymmetric advantage over much stronger incumbents. Using the case studies of the two Russian counterinsurgencies in Chechnya, the article shows the mechanisms on the ground through which Moscow’s deployment of indigenous forces against insurgents helped to stem the tide of conflict, reversing the insurgents’ initial advantage in terms of asymmetry of values